The Influence of Cinematic Therapy Short Movie in Increasing Self-esteem of Fatherless Community X Teenagers in Sepatan - Saputra, Deny Surya; Isdianto, Ine Dwi; Nika, Bulan Lutfia; Samosir, Riando Felix; Hamdani, Muhammad Naufal; Nurfitriyanti, Sandi; Nurhidayati, Annisa (Jurnal Perempuan dan Anak, 2024)
This research aims to determine whether or not there is an influence of cinematic therapy short films in increasing self-esteem among teenagers in the X community who experience fatherlessness in the Sepatan area. The research method used was experimental with a pretest-posttest control group research design and used a paired sample t-test. The sample in this study were teenagers from the X community in the Sepatan area. The results of the paired sample t-test obtained a value (p) of 0.000 in the experimental group, p<0.05 so that H1 was accepted and H0 was rejected, meaning that subjects who were given film therapy experienced an increase in self-esteem. Meanwhile, in the control group, the value (p) was 0.003, p<0.05, so H1 was accepted and H0 was rejected, meaning that subjects who were not given cinematic therapy short films also experienced an increase in self-esteem. In conclusion, cinematic therapy short films have an influence on increasing self-esteem but it is not significant